Principles on the use of imaging studies in the diagnosis and management of juvenile idiopathic arthritis - N. T. Vatutin; A. S. Smyrnova; M. A. El-Khatib (Современная ревматология)
The paper presents the basic principles on the use of imaging studies in the diagnosis and management of juvenile idiopathic arthritis (JIA), which have been elaborated by the European League Against Rheumatism (EULAR) jointly with the Pediatric Rheumatology European Society (PreS). These principles will render certain assistance to practitioners in diagnosing and treating patients with JIA. Undoubtedly, there have been no answers to many questions so far. This primarily applies to the necessity of understanding the standards for the possibility to interpret the pathological process, to harmonize the respective MRI protocols, to identify bone marrow edema, erosions, and synovitis, and to determine the suitability of these or those examinations in order to reveal changes in individual joints. There are considerable conceptual differences in approaches to diagnostic techniques in adults and children. The EULAR-PReS experts assume that some studies may be impracticable or economically inaccessible and this may hinder their introduction into clinical practice. However, most techniques, including ultrasonography, are quite affordable. The practical application of these techniques certainly requires a high professionalism of specialists in functional diagnosis and other instrumental studies.